Microscopic, pharmacognostic and phytochemical evaluation of Sesbania grandiflora leaves - Sharma, Sharad; Semwal, Bhupesh Chander; Mazumder, Avijit (Creative Pharma Assent, 2024)
Objective: Sesbania grandiflora is a short-lived and fast-growing edible ornamental plant belonging to the Fabaceae family. Due to its unique therapeutic characteristics such as anti-inflammatory, antitumor, neuroprotective antioxidant, etc., it is utilized as an herbal medication in the Indian traditional medical system to treat various diseases. Therefore, the objective of the current investigation was to offer certain beneficial information regarding the standardization and identification of S. grandiflora leaf, which may be helpful in terms of its validity, purity, and quality. Methods: The micro- and macroscopical study of fresh and dried leaves of Sesbania grandiflora was investigated. Physicochemical parameters were performed according to WHO-recommended parameters. The dried leaves were powdered and extracted with different solvents in a Soxhlet apparatus. The concentrated extract was further used for physiochemical and phytochemical studies. Result: The fresh leaves of S. grandiflora were examined for their organoleptic characteristics. The leaves are regular compound and pari-pinnate with an average length of 15–30 cm long with green color. The transverse section of the leaf demonstrated the presence of spongy and palisade type of mesophyll cells. Stomata are anxiolytic and anisocytic stomata. Furthermore, Powder microscopy revealed the presence of simple epidermal hairs, dark yellowish-brown tannin fragments, light yellowish resinoids, oil globules, mucilage cells, and spiral vessels. Phytochemical screening revealed the presence of triterpenes, glycosides, tannins, flavonoids, gallic acid, biotin, and rutin. Conclusion: This study adds to the body of knowledge regarding the standardization and identification of the subject matter and facilitates future research on the Ayurvedic medical system.